Analysis of the Role of Teachers in Arts and Culture Learning for Grade IV Students of SD Inpres 8 Mamboro - Tepaso, Avelia; Lagandesa, Yun Ratna; Aqil, Muhammad; Hariana, Kadek; Pahriadi, Pahriadi (Journal of Educational Sciences, 2025)
This research aims to describe the role of teachers in SBdP (Arts, Culture, and Craft) learning for fourth-grade students at SD Inpres 8 Mamboro. The background of this study arises from various learning difficulties faced by students, both internally and externally, which affect their interest and motivation in SBdP lessons. A descriptive qualitative approach was employed, using observation, interviews, and documentation as data collection techniques. The research subjects included fourth-grade teachers and students. The results revealed that the teacher plays an essential role as a facilitator, learning manager, motivator, guide, and demonstrator. The teacher provides engaging learning media, creates a positive and creative classroom atmosphere, and encourages students to express their ideas confidently. Furthermore, the teacher gives direct guidance to students who face difficulties, uses various teaching strategies, and applies concrete examples to make the material easily understood. This study concludes that an active and creative teacher significantly contributes to students’ learning success in SBdP. The teacher’s ability to understand students’ characteristics, adapt strategies, and maintain an interactive learning environment enhances students’ interest and learning outcomes. Therefore, the teacher’s role is crucial in overcoming learning difficulties and fostering students’ creativity and motivation in SBdP lessons.